Exploring Families’ Experiences in Supporting Older Adults’ Care in the Community: A Community Nursing Perspective - Hikmawati; Nasir Muna (Jurnal Ilmu Kesehatan Nusantara, 2025)
Background: Population ageing increases families’ responsibilities for providing long-term care to older adults in the community. However, family caregivers frequently perform complex tasks with limited knowledge, resources, and professional assistance. Research Objective: This study explored families’ experiences in supporting older adults’ care in Buton Regency from a community nursing perspective. Methods: A qualitative descriptive study involved 15 family caregivers recruited through purposive sampling. Data were collected using semi-structured interviews and field notes. Interviews were transcribed verbatim and analysed thematically. Trustworthiness was established through member checking, peer discussion, reflexive notes, contextual descriptions, and an audit trail. Results: Five themes emerged: caregiving as a moral and cultural responsibility; families as coordinators of everyday care; multidimensional caregiving challenges; adaptation, spirituality, and shared family support; and the need for accessible, family-centred community nursing. Participants provided care, managed medication and nutrition, monitored symptoms, and made healthcare decisions. However, they experienced fatigue, emotional strain, financial pressure, limited caregiving knowledge, and geographical barriers. Conclusion: Families constitute the foundation of community-based older-adult care but require structured professional support. Community nurses should provide regular home visits, practical education, caregiver assessment, accessible consultation, and coordinated referrals to improve care quality and caregiver well-being.